Numerical Taxonomy of Rapidly Growing, Scotochromogenic Mycobacteria of the Mycobacterium parafortuitum Complex: Mycobacterium austroafricanum sp. nov. and Mycobacterium diernhoferi sp. nov., nom. rev. - TSUKAMURA, MICHIO; VAN DER MEULEN, HERMINA J.; GRABOW, WILHELM O. K. (International Journal of Systematic and Evolutionary Microbiology, 1983)
A numerical analysis of phenetic data collected from rapidly growing, scotoch-romogenic mycobacterial strains isolated from water in South Africa and from strains of the taxa Mycobacterium parafortuitum, Mycobacterium aurum, Mycobacterium neoaurum, and “Mycobacterium diernhoferi” indicated that all of these organisms belong to the Mycobacterium parafortuitum complex. Our results also indicated that each of the taxa mentioned above is worthy of species status within the complex. The name Mycobacterium austroafricanum sp. nov. is proposed for the South African isolates, and the characteristics of these isolates are described; the type strain is E9789-SA12441 (= ATCC 33464). The name Mycobacterium diernhoferi is revived for the organism described originally by Bönicke and Juhasz in 1965; the type strain of this species is strain 41001 (= ATCC 19340).